2005
DOI: 10.1080/13658810500106729
|View full text |Cite
|
Sign up to set email alerts
|

Using uncertain conceptual spaces to translate between land cover categories

Abstract: To support diversified uses of geographical information there is a need for enhanced spatial data infrastructures to create interoperability between users and prod.ucers of geographic data. One important interoperability problem is caused by dlfTerences in data semantics, for example heterogeneous land use/land cover ~lassification systems. A critical review of an existing method for semantic mteroperability between land cover classifications is used to motivate and introduce a modified framework based on conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 17 publications
(26 reference statements)
0
53
0
Order By: Relevance
“…To reveal the inherent ill-posedness of “conceptual matching” between two categorical variables A and B investigated by Ahlqvist (2005) (refer to the Part 1, Chapter 4), one co-author of this paper, different from the independent human expert (refer to Acknowledgments), conducted a second inherently equivocal selection of “correct” entry-pairs in a binary relationship, R: A ⇒ B ⊆ A × B, to guide the interpretation process of the OAMTRX = FrequencyCount(A × B) instance shown in Table 4. This second experiment provided an mDMI pair of O-Q 2 Is equal to OA(OAMTRX = FrequencyCount(A × B)) = 97.28% ± 0% and CVPAI2(R: A ⇒ B) = 0.6731.…”
Section: Validation Sessionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reveal the inherent ill-posedness of “conceptual matching” between two categorical variables A and B investigated by Ahlqvist (2005) (refer to the Part 1, Chapter 4), one co-author of this paper, different from the independent human expert (refer to Acknowledgments), conducted a second inherently equivocal selection of “correct” entry-pairs in a binary relationship, R: A ⇒ B ⊆ A × B, to guide the interpretation process of the OAMTRX = FrequencyCount(A × B) instance shown in Table 4. This second experiment provided an mDMI pair of O-Q 2 Is equal to OA(OAMTRX = FrequencyCount(A × B)) = 97.28% ± 0% and CVPAI2(R: A ⇒ B) = 0.6731.…”
Section: Validation Sessionmentioning
confidence: 99%
“…Chapter 2 describes materials including the SIAM computer program, the time-series of annual WELD image composites, the reference USGS NLCD 2006 map and the EPA Level III ecoregion map of North America. Methods, specifically, an original protocol to compare without sampling the test SIAM-WELD map and the reference USGS NLCD 2006 map of the CONUS, whose map legends do not coincide and must be harmonized (reconciled, associated, translated) (Ahlqvist, 2005), is proposed in Chapter 3. Experimental results are presented in Chapter 4 and discussed in Chapter 5.…”
Section: Introductionmentioning
confidence: 99%
“…Ahlqvist writes that “to negotiate and compare information stemming from different classification systems (Bishr, 1998; Mizen, Dolbear, & Hart, 2005)… a translation can be achieved by matching the concepts in one system with concepts in another , either directly or through an intermediate classification (Feng & Flewelling, 2004; Kavouras & Kokla, 2002)” (Ahlqvist, 2005). Stehman describes four common types of thematic map-pair comparisons (Stehman, 1999).…”
Section: Original Hybrid Eight-step Guideline For Identification Of Amentioning
confidence: 99%
“…Whereas a large portion of the RS community appears concerned with the aforementioned first type of map comparisons exclusively, the protocol proposed in (Baraldi et al, 2014) focuses on the second type, which includes the first type as a special case. In Couclelis (2010), the author observed that inter-dictionary concept matching (“conceptual matching”) (Ahlqvist, 2005) is an inherently equivocal information-as-data-interpretation process (Capurro & Hjørland, 2003), see Table 3. In common practice, two independent human domain-experts (cognitive agents, knowledge engineers) are likely to identify different binary associations between two codebooks of codewords (Laurini & Thompson, 1992).…”
Section: Original Hybrid Eight-step Guideline For Identification Of Amentioning
confidence: 99%
See 1 more Smart Citation